An annotated checklist of centipedes (Chilopoda) of Middle Asian countries, part 1. Lithobiomorpha - Dyachkov, Yurii V.; Farzalieva, Gyulli Sh.; Tuf, Ivan H. (Zootaxa, 2022)
The first part of an annotated checklist of the centipede fauna of five Middle Asian countries (Kazakhstan, Uzbekistan, Turkmenistan, Tajikistan, Kyrgyzstan) based on literature data critically revised, is here presented. The check-list includes 49 species of Lithobiomorpha arranged in 10 genera and 3 families (Anopsobiidae, Henicopidae, and Lithobiidae). Two monotypic genera (Dzhungaria Farzalieva, Zalesskaja & Edgecombe, 2004 and Ghilaroviella Zalesskaja, 1975) and 31 species are known from Middle Asian countries only; 3 species are regarded as introduced in the region. The data on habitat records within Middle Asian countries and remarks for each species are provided. Bothropolys rugosus (Meinert, 1872), from the western Palaearctic and Malesian Region, and Lithobius potanini Sseliwanoff, 1881, from the Xinjiang Uygur Autonomous Region (China), were excluded from the fauna of the study area. The history of the studies on the lithobiomorph centipede fauna of the Middle Asian countries is provided.